Mussels and clams from the italian fish market. is there a human exposition risk to metals and arsenic?. (March 2018) - Chiesa, L.M.; Ceriani, F.; Caligara, M.; Di Candia, D.; Malandra, R.; Panseri, S.; Arioli, F.
Abstract: Seafood is associated with many beneficial effects on human health. However, the overall level of contaminants in biota has increased over the last two centuries and seafood is one of the source of oral exposition to contaminants. Therefore, this work aimed to evaluate cadmium, lead, mercury, arsenic, chromium and nickel presence in mussels and clams, from the Italian market, and the associated risk. The samples were from five different FAO areas. Analyses were carried out using inductively-coupled plasms-mass spectrometry. The sample concentrations were below the maximum levels stated by Commission Regulation (EC) 1881/2006, except one mussel sample, which was non-compliant for cadmium (2.13 ± 0.20 mg kg −1 ). For arsenic, nickel and chromium, maximum levels are not stated by the European Union. In this study, arsenic ranged from 1.29 to 13.35 mg kg −1 and nickel ranged from <LOQ−3.98 mg kg −1, except one sample, whose nickel concentration was 21.70 mg kg −1 . Chromium was found only in 15 samples, with a maximum concentration of 2.81 ± 0.27 mg kg −1, in one clam sample. Our results indicate that the average Italian consumption of molluscs, does not pose a risk for consumers, except nickel, which can cause allergic dermatitis in nickel-sensitive individuals. However a particular concern is caused by the exposition to As of the 95th percentile consumers: the Hazard Index for skin lesions, was >1, and BMDL10 for lung bladder and skin cancer in all mussel samples was overcome, in the 100% and 25% of mussel and clam samples, respectively. Graphical abstract: Highlights: Mussels and clams are filter feeders that can bioaccumulate various chemicals. Seafood metal contamination is a recognized public health risk. The presence of metals and arsenic in these molluscs from Italian market was checked. A very low risk for the consumer health emerged due to the intake of molluscs. Allergic dermatitis in Ni-sensitive subjects may be induced by all analysed samples.